2018
DOI: 10.1108/ils-06-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

Principles and practice in impact assessment for academic libraries

Abstract: Purpose This paper aims to examine the principles that underpin library assessment, methods used for impact and performance evaluation and how academic libraries should use the findings, and it discusses how value frameworks help. Design/methodology/approach This is a literature review covering aspects of value (value propositions, value co-creation), value frameworks (including the 2015 ACRL framework, Holbrook typology with worked example), data analytics and collaborative projects including LibQUAL+ initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
12
0
2
Order By: Relevance
“…A culture of evidence based practice within an organizational or workplace context requires a shared approach and requires all library staff (Hallam & Partridge, 2006;Urquhart, 2018). Library leadership in evidence based practice is also essential to achieving its aims.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A culture of evidence based practice within an organizational or workplace context requires a shared approach and requires all library staff (Hallam & Partridge, 2006;Urquhart, 2018). Library leadership in evidence based practice is also essential to achieving its aims.…”
Section: Resultsmentioning
confidence: 99%
“…Library leadership and a customer-centered organizational culture were two of the enablers that supported the development of evidence based practices in libraries (Hiller et al, 2008). Urquhart (2018) stressed that implementing a culture of assessment, or evidence based practice, requires all library staff, not just managers, to appreciate the importance of the qualitative and quantitative evidence that they gather and to understand how such evidence can help demonstrate the value of library services. Gillespie, Partridge, Bruce, and Howlett (2016) found that a shared organizational approach to evidence based practice, whether intentionally sought or not, guided and developed library services and collections, helped to build relationships with its clients, and ensured that services aligned with clients' needs through an attitude and culture of continuous improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Library leadership and a customer-centred organisational culture were two of the enablers that supported the development of evidence-based practices in libraries (Hiller, Kyrillidou, & Self, 2008). A culture of evidencebased practice, requires all library staff, not just leaders, to appreciate the importance of the qualitative and quantitative evidence that they handle and to understand how such evidence can help demonstrate the value of library services (Urquhart, 2018). Shared organisational approaches to evidence-based practice, guide and develop library services and collections through an attitude and culture of continuous improvement (Gillespie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A synthesis of prior research findings revealed that the assessment methods most commonly used by libraries include surveys/questionnaires, focus group interviews, usability studies, transaction log analysis, process analysis/ improvement studies, facility studies and card sorting tests (Covey, 2002a, b;Wright and White, 2007). While these assessment tools are essential for assessing library services, none can measure the impact of libraries on students' learning outcomes, which is important to the administrators of educational institutions (Kyrillidou and Cook, 2008;Leonard, 1992;Oakleaf, 2012;Powell, 1992;Urquhart, 2018). To overcome this limitation, Wong and Webb (2011) approached library assessment differently.…”
Section: Statements Disagree Agreementioning
confidence: 99%